Analisa Sistem Informasi Penjualan Kacamata - Ajeng Hidayati; Ade Julian (IMTechno: Journal of Industrial Management and Technology, 2020)
Sales transactions in the trade sector are very much in need of an information system that supports and provides satisfactory service to customers. For this reason, researchers conducted research on the cash eyewear sales information system on an optic, which until now has not been computerized. Optics as a research object is engaged in the sale of prescription and non-prescription glasses. The system design is limited to the eye examination process, the glasses order process, the payment process and the glasses sales report. With the existence of computerization, it is hoped that it can help the processing of sales data, both searching and storing data, become easier and faster. The calculation process in making eyewear sales reports is more timely, and minimizes errors so that it can simplify and speed up work to be faster, more effective and efficient. Therefore, so that the system can run well, the results of this study provide a form of proposal and proposal documents as well as program design.